Advances in understanding the pathogenesis of graft‐versus‐host disease. (27th March 2016) - Magenau, John; Runaas, Lyndsey; Reddy, Pavan
Summary: Allogeneic haematopoietic stem cell transplantation (HCT) is a potent immunotherapy with curative potential for several haematological disorders. Overcoming the immunological barrier of acute graft‐versus‐host disease (GVHD) remains a fundamental impediment to expanding the efficacy of HCT. GVHD reflects a complex pathological interaction between the innate and adaptive immune systems of the host and donor. Over the past decade there has been a tremendous advancement in our understanding of the cellular and molecular underpinnings of this devastating disease. In this review, we cover several recently appreciated facets of GVHD pathogenesis including novel extracellular mediators of inflammation, immune subsets, intracellular signal transduction, post‐translation modifications and epigenetic regulation. We begin to develop general themes regarding the immunological pathways in GVHD pathogenesis, discuss critical outstanding questions, and explore new avenues for GVHD treatment and prevention.